All Days 2016
DOI: 10.2118/180460-ms
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Optimal Frac Design Parameters for Asymmetric Hydraulic Fractures as a Result of Interacting Hydraulic and Natural Fractures - Application to the Eagle Ford

Abstract: Estimation of permeability in the Stimulated Reservoir Volume (SRV) is a vital input in any completion optimization workflow. One method to estimate the stimulated permeability in the SRV is to couple geomechanical modeling of the interaction between hydraulic and natural fractures with hydraulic fracture mechanics commonly used to design frac jobs. The proposed approach starts by deriving strain resulting from the integration of geological, geophysical and geomechanical modeling of interacting hydraulic and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 12 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The HF-NF interaction study results in a permeable pre-existing NF with a fingerlike crack were shown to have substantial insignificant effect of poroelasticity on changes in injected fluid pressure in the using Green's function approach (Sarvaramini and Garagash 2016). Paryani et al (2016) also combined a pseudo 3D asymmetrical frac design with 2D strain map to analytically and numerically determine the influence of frac design parameters. The authors concluded that the most influential parameters affecting the longer side of asymmetric fracture wing are drainage area, fracture height, and reservoir permeability, while the influential parameters affecting the shorter side of asymmetric fracture wing are stress gradient, fracture height, and reservoir permeability.…”
Section: Methods Of Approachmentioning
confidence: 99%
“…The HF-NF interaction study results in a permeable pre-existing NF with a fingerlike crack were shown to have substantial insignificant effect of poroelasticity on changes in injected fluid pressure in the using Green's function approach (Sarvaramini and Garagash 2016). Paryani et al (2016) also combined a pseudo 3D asymmetrical frac design with 2D strain map to analytically and numerically determine the influence of frac design parameters. The authors concluded that the most influential parameters affecting the longer side of asymmetric fracture wing are drainage area, fracture height, and reservoir permeability, while the influential parameters affecting the shorter side of asymmetric fracture wing are stress gradient, fracture height, and reservoir permeability.…”
Section: Methods Of Approachmentioning
confidence: 99%
“…Therefore, the theory of probability is brought into use. The basic parameter values and their regularity of distribution are gained from a typical shale oil and gas field, taking Eagle Ford as an example [24][25][26][27]. And the Monte Carlo random sampling method is used to determine a large number of parameter combinations, with which the distribution of duration time of compound linear flow can be calculated and an analysis can be done.…”
Section: Validation Of the Duration Time Of Linear Flowmentioning
confidence: 99%
“…The MPM is an example of a meshless method [41] as the mesh is not required for a full description of the material, it is only used for calculation purposes. The proposed MPM workflow [42,43] reduces uncertainties in fracture design and optimization through the use of half lengths derived from the validated geomechanical strain.…”
Section: Discrete Fracture Network Models and Limitationsmentioning
confidence: 99%